2021
DOI: 10.1371/journal.pone.0260395
|View full text |Cite
|
Sign up to set email alerts
|

Detecting fabrication in large-scale molecular omics data

Abstract: Fraud is a pervasive problem and can occur as fabrication, falsification, plagiarism, or theft. The scientific community is not exempt from this universal problem and several studies have recently been caught manipulating or fabricating data. Current measures to prevent and deter scientific misconduct come in the form of the peer-review process and on-site clinical trial auditors. As recent advances in high-throughput omics technologies have moved biology into the realm of big-data, fraud detection methods mus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Targeted gene research may represent an attractive topic for paper mills because the associated experimental results are easy to fabricate (Figure 2 ). In contrast to the fabrication of genome-wide research that has been estimated to require similar effort as the acquisition of genuine data ( 74 ), targeted gene research is easier to fabricate than to produce through genuine effort ( 27 , 38 ) (Figure 2 ). Targeted gene research uses experimental techniques that generate small individual datasets that are easy to invent, with access to only basic text and image processing software.…”
Section: Why Human Gene Research Could Be Particularly Vulnerable To ...mentioning
confidence: 99%
“…Targeted gene research may represent an attractive topic for paper mills because the associated experimental results are easy to fabricate (Figure 2 ). In contrast to the fabrication of genome-wide research that has been estimated to require similar effort as the acquisition of genuine data ( 74 ), targeted gene research is easier to fabricate than to produce through genuine effort ( 27 , 38 ) (Figure 2 ). Targeted gene research uses experimental techniques that generate small individual datasets that are easy to invent, with access to only basic text and image processing software.…”
Section: Why Human Gene Research Could Be Particularly Vulnerable To ...mentioning
confidence: 99%
“…Unlike images, data fabrication in numerical tables can be subtle and hard to detect. In 2020, Bradshaw and Payne examined methods to detect fabricated numerical omics data, 126 concluding that methods originally developed to detect fraud in banking and insurance would be applicable to scientific data.…”
Section: Research Integritymentioning
confidence: 99%
“…Manipulated or fabricated data can be detected by a variety of algorithms leveraging number theory metrics unrelated to study design, such as Benford’s Law 130 used by Bradshaw and Payne, 126 and Zipf’s Law. 131 The workshop demonstrated that some existing models for predicting mass spectra violate some of these laws.…”
Section: Research Integritymentioning
confidence: 99%
“…We used t-statistics to test for issues in baseline tables, but other methods could be applied such as Benford's law [22,43].…”
Section: Relation Previous Workmentioning
confidence: 99%